As obrigações acessórias na previdência social brasileira - Barreto, Ana Carolina Rossi (2007)
This paper has the intention of presenting the accessory obligations provisioned by the social security legislation; to establish their purpose, justify their concepts, and to demonstrate their importance within the scope of the Brazilian social security. It also intends to demonstrate that, with the Federal Constitution of 1988 abandoning the adoption of the concept of a Constitution directed to the state adopting a Constitution directed to Society and here, specifically regarding accessory obligations, there was the emergence of multiple effects, among them the requirement that these meet their finality content, which is, the interest of the tax collection or of the inspecting authorities .Regarding their concept and delimitation, it can be seen that there are conflicts in the doctrine on nomenclature, so that the values and principles brought by the Federal Constitution of 1988, which in their force, allow imparting effectiveness to the compliance and development of the social protection programs. For this, seeking to improve the reader s understanding within this universe, first there is a study of the financing of the Brazilian Social Security, the concept and the features of the social contributions directed to it, as well as the composition of its legal relation